PERAN KOMUNITAS PEREMPUAN KECAMATAN TANJUNG BINTANG DALAM PENGEMBANGAN UMKM (STUDI PADA UMKM BINAAN DINAS KOPERASI DAN UMKM LAMPUNG SELATAN) - Lisa, Ellyas; Suryani, Eny Inti; Islam, Nur (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2024)
Empowering women in developing Micro, Small and Medium Enterprises through MSMEs is an important focus, especially in the context of the women's community in Tanjung Bintang District, South Lampung. Tanjung Bintang District is the focus of the study which shows the crucial role of the women's community in mobilizing MSMEs as a key element in supporting MSME development. This research aims to document, analyze and understand the role of the Tanjung Bintang District women's community in developing MSMEs. This research uses a qualitative approach with observation, interview and documentation study techniques. Information was obtained from the South Lampung Regency Cooperative and MSME Service, District Government Apparatus, Women's Community Administrators, MSME actors in Jati Baru Village, Jati Indah, Srikaton. The research results show that the Tanjung Bintang District women's community has a central role in the development of MSMEs. They are active in empowering village women, developing cooperation, and ensuring the sustainability of micro-enterprises. Empowering women in MSMEs has a positive impact on the economic and social improvement of village communities